Intelligence and the national security strategist enduring issues and challenges - edited by Roger Z. George (Lanham Rowman & Littlefield, 2006)
Intelligence and the National Security Strategist: Enduring Issues and Challenges presents students with a useful anthology of published articles from diverse sources as well as original contributions to the study of intelligence. The collection includes classic perspectives from the history of warfare, views on the evolution of U.S. intelligence, and studies on the delicate balance between the need for information-gathering and the values of democratic societies. It also includes succinct discussions of complex issues facing the Intelligence Community, such as the challenges of technical and clandestine collection, the proliferation of open sources, the problems of deception and denial operations, and the interaction between the Intelligence Community and the military. Several timely chapters examine the role of the intelligence analyst in support of the national security policymaker. Rounding out the volume are appendices on the legislative underpinnings of our national intelligence apparatus.
Includes bibliographical references (p. 591-592).
Keywords: Military intelligence--United States